The Influence of External Knowledge on Innovation of Start-Ups: The Mediating Role of Absorptive Capability and Opportunity Recognition Ability - Nguyen Thi, Hanh; Nguyen Duy , Hung (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
This research evaluates the role of external knowledge and the ability to absorb and recognize opportunities for entrepreneurial firms in Vietnam. Using a Partial Least Squares Structural Equation Modeling, the study tests data from a survey of more than 150 new ventures. Results show no direct relationship between external knowledge and innovation outcomes. However, knowledge absorption and opportunity recognition fully mediate the influence of knowledge diversity on innovation. Opportunity recognition mediates the effect of knowledge depth on innovation, but knowledge absorption does not. These findings contribute to open innovation theory and provide practical implications for improving innovation.